University Students’ Effortin Helping The Promotion Oforphans Personal Hygiene In A Family Counseling Practice at an Orphanage - Fitriandini, Siska; Jubaedah, Yoyoh; Rinekasari, Nenden Rani (Prodi PKK - Departemen PKK - Universitas Pendidikan Indonesia, 2016)
The background of this research is the efforts undertaken by students of PKK Education Program, in implementing their knowledge, attitudes and skills that are expected to provide social services, particularly for children inthe orphanage. These children does not know how to take care of their personal hygiene, such as dental, nails, skin and hair care. Ideally, every child should get a special attention to carry out their development tasks. The purpose of this study is to determine the efforts made by the university students in promoting the habituation of personal hygiene for children in the orphanage, after giving a counseling. The subjects of this research were the students of PKK Education Program who have takenFamily Counseling course in 2014, with 36 people as samples, including students from batch 2012 and 2013. This study used a descriptive method, and the data were collected through questionnaires.The resultof this research indicates that the efforts made by the university students in order to accustom the orphans to take care of their personal hygiene arereminding, advising, givingexamples of how to take care of personal hygiene, showing equipments and materials used to take care of personal hygiene in the form of real equipment and materials and in the form of pictures, providing simulations, demonstrations, and discussionon how to care for themselves properly, providing elaborations, informing kinds of food and beverages that can maintain and damage personal hygiene, as well as giving rewards that can motivate children to perform personal hygiene.